Current Advances in Lipid Nanosystems Intended for Topical and Transdermal Drug Delivery Applications - Nakamwi Akombaetwa; Ange B. Ilangala; Lorraine Thom; Patrick B. Memvanga; Bwalya Angel Witika; Aristote B. Buya (MDPI AG, 2023)
Skin delivery is an exciting and challenging field. It is a promising approach for effective drug delivery due to its ease of administration, ease of handling, high flexibility, controlled release, prolonged therapeutic effect, adaptability, and many other advantages. The main associated challenge, however, is low skin permeability. The skin is a healthy barrier that serves as the body's primary defence mechanism against foreign particles. New advances in skin delivery (both topical and transdermal) depend on overcoming the challenges associated with drug molecule permeation and skin irritation. These limitations can be overcome by employing new approaches such as lipid nanosystems. Due to their advantages (such as easy scaling, low cost, and remarkable stability) these systems have attracted interest from the scientific community. However, for a successful formulation, several factors including particle size, surface charge, components, etc. have to be understood and controlled. This review provided a brief overview of the structure of the skin as well as the different pathways of nanoparticle penetration. In addition, the main factors influencing the penetration of nanoparticles have been highlighted. Applications of lipid nanosystems for dermal and transdermal delivery, as well as regulatory aspects, were critically discussed.